Anterior Cervical Corpectomy and the Operating Team: A Controversy? - Alexandrina Nikova; Theodossios Birbilis (Indian Journal of Neurosurgery)
Cervical myelopathy is multifactorial disease that can lead to many dysfunctions. Surgical treatment is believed to be the best healing choice. The authors searched the published data on Medline on this subject and found a difference between the neurosurgeons and orthopaedics on the topic of anterior corpectomy for cervical myelopathy. The difference between the orthopaedics and neurosurgeons is not big, but it could be relevant to the final outcome, which appears to be better in the neurosurgeons. The complication rate is also variable between the groups, with lower rates of complication reported by the neurosurgeons. Therefore, despite the fact that the postoperative outcome depends on many factors, such as preoperative condition, additional comorbidities, age, and lifestyle, this article also finds that the surgical team, after comparing basic techniques that the team used for anterior cervical corpectomy (ACC), is also responsible to some extent. This, however, is not a competition, and future cooperation between the teams might be beneficial for all.